The ambivalent links between internal migration and food security in Uganda - Mekonnen, Daniel A.; Soma, Katrine; Ruben, Ruerd (SAGE Publications, 2022)
This study examines the drivers for and consequences of internal migration to household food security in Uganda. Based on the Ugandan National Panel Surveys conducted between 2010/11 and 2015/16, we estimate differences in food energy adequacy of households receiving internal migrants from elsewhere. Besides food energy consumption, this study applies household food consumption score (FCS) and looks at vulnerability in terms of household’s expenditures on food. This enables to explore (a) the extent to which food insecurity is driving internal migration, and (b) whether remittances can reduce food security of the remitter. We find that households are usually worse-off when migrants join the receiving family. This seems a departure from previous studies that tend to find welfare gains to internal migration, mostly due to changes in expenditures or dietary consumption without considering any thresholds for achieving food security. Based on these findings and responding to rising youth employment challenges associated with rapidly growing urban slums in Uganda, policies that simultaneously support employment creation in both urban and rural areas are urgently needed to enable better steering of the flow of voluntary migration and to help ensuring food security.